2018
DOI: 10.1002/ets2.12233
|View full text |Cite
|
Sign up to set email alerts
|

Domain Description: Validating the Interpretation of the TOEFL iBT® Speaking Scores for International Teaching Assistant Screening and Certification Purposes

Abstract: In the past 2 decades, there has been an increasing tendency to use scores from the TOEFL iBT® Speaking test for decisions regarding the certification of international graduate students as teaching assistants at North American universities. To obtain validity evidence in support of the usefulness of the speaking scores for this secondary use of the test, this study adopted the argument‐based approach to validation. Focusing on the domain description inference in the TOEFL interpretive argument, the study inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…The TOEFL iBt speaking test has been subject to ongoing validation studies. Some studies (e.g., Bridgeman et al, 2012;Cotos & Chung, 2018;Cumming et al, 2005;Enright & Tyson, 2008;Ockey et al, 2015) have examined the alignment between the test and TLUS tasks and reported TOEFL iBT to be a valid measure of communicative ability owing to setting up an actual situation requiring applicants to demonstrate their capacity to perform various TLUS tasks in the test. Cotos and Chung (2018) sought to explore to what extent the language functions elicited by TOEFL iBT speaking tasks are in line with those fulfilled by international teaching assistants in the authentic discourse.…”
Section: Toefl Ibt Speaking Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The TOEFL iBt speaking test has been subject to ongoing validation studies. Some studies (e.g., Bridgeman et al, 2012;Cotos & Chung, 2018;Cumming et al, 2005;Enright & Tyson, 2008;Ockey et al, 2015) have examined the alignment between the test and TLUS tasks and reported TOEFL iBT to be a valid measure of communicative ability owing to setting up an actual situation requiring applicants to demonstrate their capacity to perform various TLUS tasks in the test. Cotos and Chung (2018) sought to explore to what extent the language functions elicited by TOEFL iBT speaking tasks are in line with those fulfilled by international teaching assistants in the authentic discourse.…”
Section: Toefl Ibt Speaking Testmentioning
confidence: 99%
“…Some studies (e.g., Bridgeman et al, 2012;Cotos & Chung, 2018;Cumming et al, 2005;Enright & Tyson, 2008;Ockey et al, 2015) have examined the alignment between the test and TLUS tasks and reported TOEFL iBT to be a valid measure of communicative ability owing to setting up an actual situation requiring applicants to demonstrate their capacity to perform various TLUS tasks in the test. Cotos and Chung (2018) sought to explore to what extent the language functions elicited by TOEFL iBT speaking tasks are in line with those fulfilled by international teaching assistants in the authentic discourse. They concluded that "TOEFL iBT speaking tasks elicit most of the language functions identified in the discourse, suggesting that this test accounts for the functional language ability necessary for effective instructional performance as a teaching assistant in the target domain of language use" (p.1).…”
Section: Toefl Ibt Speaking Testmentioning
confidence: 99%